Challenges for Adaptation of Business Management - Kucsma, Daniella (International Journal of Engineering and Management Sciences, 2017)
Both the business management and the public sector try to provide employee with providing jobs, which are esteemed by the workforce and where employee has a good feeling. However the public management has a big challenge in this area, because the bussiness sector is more attractive, and competitive pay for emloyees. I tested the bussiness modell and look for their benefits and I saerch for connectivity points. This point will helps into the adaption to the non- bussiness sector.